KARAKTER PEDULI SOSIAL MAHASISWA PENERIMA BEASISWA PRODUKTIF BAZNAS DALAM UPAYA TANGGAP BENCANA DI KOTA SEMARANG (Civic Education Program, Universitas Negeri Semarang, 2022)
The social care character of Baznas productive scholarship recipients in disaster response is an effort made by Baznas recipient students to help disaster response efforts in the city of Semarang. The purpose of this research is to find out (1) what activities in disaster response efforts by baznas students in Semarang City, (2) The character of social care care what is in disaster response efforts in the city of Semarang, (3) the factor inhibits the activity of social care of baznas productive scholarship students in disaster response efforts in Semarang City.. This research method is qualitative research. Research data sources include primary and secondary data sources. Data collection tools and techniques in the form of observations, interviews and documentation. Data validity test using source triangulation techniques and qualitatively analyzed techniques that include data collection; data reduction; presentation of data; and conclusions. The results showed that baznas productive scholarship students already partially have a social care character related to social care activities such as in terms of his (a) empathy in the soup kitchen, (b) Evacuation of flood victims in help, (c) Loyalty in the provision of social assistance, (d) Service Work in devotion, (e) Landslide survey in cooperation, (f) Student Training as a form of discipline, (g) Monthly picket as a form of family. Inhibiting factors in student social care activities are different student lecture schedules, incomplete facilities, location of flood disasters that are difficult to reach and Lack of Communication. The conclusion of the research is that baznas productive scholarship students carry out the character of social care through social activities in the community. Advice for students participating in disaster response activities and advice for Baznas is expected to encourage students well.